500 tips on group learning - Race, Philip (London ; Sterling, VA : Kogan Page Limited, 2000)
Including sections on creative thinking, problems in groups, feedback mechanisms, dealing with conflict, and gender issues within groups, this volume is designed to aid educators and trainers to create more effective group learning situations.
Chapter 1. Learning with others -- 1. Learning about learning -- 2. Group learning means learning by doing -- 3. Group learning means learning through feedback -- 4. Things going wrong can be good group learning -- 5. Group learning means motivation...wanting to learn -- 6. Behaviors of a good leader -- 7. Group learning includes following -- 8. Benefits of group learning -- Chapter 2. Getting groups going -- 9. Preparing learners for group work -- 10. Ways of forming groups -- 11. Group size considerations -- 12. Getting groups started -- 13. Icebreakers: some ideas -- 14. Establishing ground rules for groups -- 15. Reducing the bystander effect -- 16. Creating group cohesion -- 17. Setting shared goals -- Chapter 3. Particular group learning contexts -- 18. Tutorials -- 19. Tutorials for adult distance learners -- 20. Home groups -- 21. Action learning sets -- 22. Tutorless groups -- 23. Be a group member yourself -- 24. Team teaching -- Chapter 4. Exercises and processes for groups -- 25. Ringing the changes -- 26. Post-it exercise on how people learn -- 27. Feedback exercise for groups -- 28. Post-its and flipcharts -- 29. Helping learners to write reflections on group learning -- 30. Virtual group work -- 31. A case study -- Chapter 5. Groups behaving badly? -- 32. Group member behaviors that damage group work -- 33. Group facilitator behaviors that can damage group work -- 34. Institutional factors that can damage group work -- 35. Conflict in group work -- 36.Gender issues in group work -- Chapter 6. Assessing group learning -- 37. Take the simplest path -- 38. Divide and conquer -- 39. Add differentials -- 40. Add contribution marks -- 41. Add more tasks -- 42. Test them orally -- 43. Test them in writing.
Includes bibliographical references and index.
Keywords: GROUP WORK IN EDUCATION